The amusement park mystery - Warner, Gertrude Chandler, 1890-1979.; Tang, Charles (New York : Scholastic, 1992)
The Aldens search for carousel horses that have disappeared from an amusement park.
Keywords: Boxcar children (Fictitious characters) -- Juvenile fiction; Orphans -- Juvenile fiction; Family -- Juvenile fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Amusement parks -- Fiction; Mystery and detective stories; Mystery fiction